Effects of water shortage stress on the morphology and expression of the gene encoding dihydrodipicolinate synthase (DHDPS) in Mesembryanthemum crystallinum - Hồng, Hoàng Thị Kim; Trang, Phạm Thị Hồng; Phượng, Trương Thị Bích; Thủy, Nguyễn Thị Thu; Thu, Ngô Thị Minh; Trang, Nguyễn Thị Quỳnh (Vietnam Journal of Biotechnology, 2018)
Lysine biosynthesis in plants has been studied extensively in order to improve the nutritional quality and provide the lysine for human life. In this process, dihydrodipicolinate synthase (DHDPS) is one of the important enzymes that determine the accumulation of lysine in plants. This paper presents the initial results of the effect of water stress on morphology and expression of gene encoding dihydrodipicolinate synthase (DHDPS) in Mesembryanthemum crystallinum leaves. M. crystallinum mature leaves have a lot of bladder cells which are surrounded and coated as the dewdrops sparkling on the outside of the leaves and twigs. When the external bladder cells of mature leaves were removed we can see a lot of stomata at both sides of the leaves under microscope with the objective lens 40 (Nikon, Eclipse 55I POL). When water stress treated after 5 days and 10 days, leaf morphology, cytoplasm and stomata of M. crystallinum mature plants were changed comparing with the control plants. The RNA was extracted from M. crystallinum leaves of both treated and untreated stress water samples. These RNA were used as a template to synthesize cDNA and analysis with specific primers by reverse transcription quantitative polymerase chain reaction (qRT-PCR). The results showed that water stress treatment had caused a change in the gene expression of DHDPH in treated plants significantly reduced the DHDPS gene expression in M. crystallinum leaves. In addition, a significant amount of DHDPS enzyme was measured in M. crystalium leaves, and the activity of that was changed by different water-stress treatment times.